Emotional Language in Madurese Culture: Implications for Culturally Responsive Counseling Practice - Diana Vidya Fakhriyani; Beny Dwi Pratama; Ishlakhatus Sa’idah; Fahmi Assulthoni (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Knowledge of culturally influenced emotionality is an important set of knowledge for culturally responsive counseling practice. Culture influences the perception, control, and expression of emotions not least within counselling where much emphasis is laid on sensitivity to cultural norms and values. The purpose of this research is to describe forms of emotional languages in Madurese culture and discuss the implications for culturally responsive counseling. This study uses a descriptive qualitative approach, where data is obtained through literature review, interviews, observation, and documentation. The results of this study show that the Madurese people manifest their feelings to others directly (blak-blakan) and indirectly using symbolic language with the values of dignity (martabat), propriety (tengka), patience (sabbhar), and social solidarity. An understanding of these ways of communicating emotions is critical in counseling for the development of therapeutic relationships that are both effective and culturally sensitive. The study suggests the need for integrating more empathy, contextually and culturally sensitive training approach that takes into consideration local value system as well as the need to tailor interventions to reflect local cultural sensitivities as a way of improving the effectiveness of psychological support.